Analysis of High Voltage High Power Resonant Converters - Bhuvaneswari C; R. Samuel Rajesh Babu (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
Various Resonant Converters for high voltage and high power applications have been designed. Different Topologies of LLC, LCC, and CLL Resonant Converters have been simulated and compared for the same input voltage. The simulation was done at a very high frequency. The Output Power and the Efficiency of all the three Resonant Converters were calculated.With the results, it has been proved that LCC Resonant Converters were very much suited to give an output voltage of around 62 Kilovolts with a output power of 20 kilowatts.